Reserves, money supply and prices: The international adjustment mechanism in Sweden under the silver and gold standards, 1834 - 1913 - Anders Ögren (Stockholm School of Economics, The Economic Research Institute (EFI), 2003)
This paper explores how international capital movements affected the domestic money supply. This requires that the causality at work in the adjustment process be analyzed. For this purpose, series of central bank reserves, the monetary base, the money supply and the balance of payments were constructed. The methodological problems encountered in estimating such monetary measures in a transitional economy where much of the circulating money consists of private banks notes, and which is dependent on foreign loans, is discussed. The relationship between central bank (Riksbank) reserves and international capital flows is then studied. The overall growth of the money supply, while not accompanied by a growth in reserves, is found to correspond to such growth in other countries operating under a specie standard. This growth also was related to the growth of the real economy. Qualitative evidence aside, statistical results indicate a relationship among reserves, the money supply and prices that is consistent with the price specie flow mechanism. Changes in reserves were positively related to the money supply and changes in the money supply had a lagged positive effect on changes in the level of consumer prices.
Keywords: E31; E51; N13; N23; 330; Balance of Payments; Central Bank Reserves; Classical Silver and Gold Standards; Monetary Base; Money Supply; Prices; Kapitalmobilität; Geldmenge; Schweden